O impacto da política de inovação sobre o trabalho do professor-pesquisador da Universidade de São Paulo, campus Ribeirão Preto - Sacramento, Leonardo Freitas (2015)
This study aims at analyzing the constraints in the work of the professor-researcher in regard with the innovation policies. The hypothesis is that the current innovation policies progressively link the work of the professor-researcher to the business sector. In order to analyze the hypothesis, the political and institutional relations of the University of São Paulo were studied, more precisely in the campus of Ribeirão Preto, as well as their articulations with public-private sectors and partnerships. Documentary analyses and data collection on innovations, applied researches, incubator companies and productions and service rendering interpreted by the area of Science and Technology were held, as well as four semistructured interviews with innovation agents. It was found that the University of São Paulo constituted its own institutional arrangements by means of articulations with institutions specifically in the municipality of Ribeirão Preto. Furthermore, institutions of the university are relevant in this process, such as USP Agency of Innovation. However, it was found that Fundação Instituto Polo Avançado da Saúde de Ribeirão Preto (FIPASE), a municipal foundation which supports innovation, encourages specific political and institutional devices for the incentive and development of researches applied to the demands of the business sector, in order to induce the researchers in the university to carry out certain practices of innovation. Consequently, it also induces part of the graduation research of the campus to turn into applied research centers, enabling the creation of spin-off companies. It is pointed out that these institutional arrangements for the development of the applied research, however, would not be possible without relevant changes in the professorresearchers‘ working hours, undertaken by them, based on decisions in the university which result in regulations and resolutions that make flexible and encourage the relation university-company. It can be concluded that, in spite of the narrowing of the link between the work of the professor-researcher in the Science and Technology area and the business sector, the innovation policy in the campus of Ribeirão Preto meets the interests of the academic community much more than the ones of the business sector itself, and that, in this process, contradictorily, it is the university that reconfigures itself to the patterns of the logic of the businesses, typical of the companies, rather than the companies that modify themselves or develop the practice of research and production of the technological knowledge, typical of the university and the scientific area.